CORPORATE SOCIAL RESPONSIBILITY PROGRAMME AS PART OF COMPLEMENTARY RELATIONSHIP IN HOTELS’ NETWORK: THE CASE OF HOTEL INDUSTRY IN BALI, INDONESIA - I Nyoman Indah Kusuma Dewi; I Gusti Agung Bagus Mataram (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2017)
Corporate Social Responsibility (hereinafter is referred to CSR) Programme has gained more interest from the hotel management since the increasing awareness of the customer to the notion of green hotel. CSR programme is considered as a part of complementary relationship in the hotels‟ network which is a non-business relationship. The purpose of this study is to discuss the implementation, maintenance and benefits of CSR programme in hotels’ network since there is limited number of studies that concern about exploring and understanding this topic from the network theory and business-to-business perspective. Thus the research questions include: (1) what are the reasons of hotels establishing CSR programme as part of their network of business relationship? (2) How do the implementation of CSR programme as a complementary relationship in hotels’ network? (3) What are the network elements (actors, activities and resources shared) involved in this network? (4) How do hotels nurture their CSR programme? (5) What are the benefits of hotels establishing CSR programme? This research is an exploratory research based on the interpretivist paradigm as the underlying paradigm. The inductive approach rather than deductive approach is implemented as the most appropriate research approach. The research strategy is multiple-case study since its enable the researcher to be close to the research objects and provide rich description of the phenomenon. The unit analysis or phenomenon in this study is CSR programme as part of complementary relationship in hotels‟ network. Nine hotels and their complementary organizations were selected as the cases; therefore, eighteen organizations were included. The top and middle level management participated in this study. Data was collected by utilizing the face-to-face semi-structured interview, direct observation and documentation review. Data has been analyzed through three concurrent flows of analyzing qualitative data: data reduction; data display; and conclusion drawing and verification. The finding confirms that there is an increasing awareness of hotel practitioners regarding the importance of establishing and nurturing CSR programme as the concurrent consequences of increasing customers’ awareness to the environment and community involvement. This might leads to the hotels’ competitive advantage. The main contribution of this study is to enhance the network analysis literature particularly its implementation in the hotel industry.